Bits on the Big Screen. - Russell Wintner (IEEE spectrum)
Digital cinema is poised to take the movie industry by storm with the introduction of the first specification for digital cinema in July 2005. To create the specification, the digital cinema initiatives was established by seven major studios, Disney, Fox, MGM, Paramount, Sony Pictures Entertainment, Universal, and Warner Brothers studios. The initiative set a quality threshold, specified a video compression technology and recommended uncompressed sound. Since completing the digital cinema specifications, efforts are focused on addressing the issue of conversion cost. A plan based on a virtual print fee has been proposed wherein movie studios pay the company that provides and installs their digital cinema equipment and software for each showing of a movie on the digital cinema system. While the exact figures haven't been made public, the cost to the movie studio is supposedly lower than the cost of making the equivalent number of film prints. In just five to ten years, the impact of digital cinema is likely to go far beyond the cost savings and quality improvements envisioned now, bringing moviegoers new forms of entertainment that have yet to be imagined